Comportement de populations de Medicago truncatula Gaertn. dans deux zones différentes ; relation avec les facteurs du milieu d'origine - Si Ziani Y.; Abdelguerfi A. (Systèmes sylvopastoraux. Pour un environnement, une agriculture et une économie durables, 1995)
Fifty-four natural populations of Medicago truncatula were evaluated for flowering time, and winter and spring growth at two different climatic locations (sub-humid and semi-arid), in Algeria. Differences among populations, previously grouped into distinct maturity classes, were assessed by ANOVA, while the relationship between population characteristics and altitude and annual rainfall of collection sites was investigated by simple correlation analysis. Early and mid-season populations with appreciable vegetative growth were individuated. Flowering time resulted correlated with both altitude and rainfall of collection sites in the sub-humid location and only with rainfall in the semi-arid one.
Réunion du Groupe de Travail Méditerranéen du Réseau Interrégional FAO/CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 1995/05/29-1995/06/02, Avignon (France)